Development of a Radiolabeled Peptide-Based Probe Targeting MT1-MMP for Breast Cancer Detection - Min, Kaiyin (PLoS One, 2015)
Breast cancer is one of the most frequent and aggressive primary tumors among women of all races. Matrix metalloproteinase (MMPs), a family of zinc- and calcium-dependent secreted or membrane anchored endopeptidases, is overexpressed in varieties of diseases including breast cancer. Therefore, noninvasive visualization and quantification of MMP in vivo are of great interest in basic research and clinical application for breast cancer early diagnosis. Herein, we developed a (99m)Tc labeled membrane type I matrix metalloproteinase (MT1-MMP) specific binding peptide, [(99m)Tc]-(HYNIC-AF7p)(tricine)(TPPTS), for in vivo detection of MDA-MB-231 breast tumor by single photon emission computed tomography (SPECT). [(99m)Tc]-(HYNIC-AF7p)(tricine)(TPPTS) demonstrated nice biostability and high MT1-MMP binding affinity in vitro and in vivo. Tumor-to-muscle ratio was found to reach to the highest (4.17±0.49) at 2 hour after intravenously administration of [(99m)Tc]-(HYNIC-AF7P)(tricine)(TPPTS) into MDA-MB-231 tumor bearing mice. Overall, [(99m)Tc]-(HYNIC-AF7P)(tricine)(TPPTS) demonstrated great potential for MT1-MMP targeted detection in vivo and it would be a promising molecular imaging probe that are probably beneficial to breast cancer early diagnoses.